Analyzing the impact of agricultural water-demand management on water availability in the Urubu River basin - Tocantins, Brazil - Nicole John Volken; Ricardo Tezini Minoti; Conceição Maria de Albuquerque Alves; Fernán Enrique Vergara (Revista Ambiente & Água, 2022)
The Urubu River is part of the Formoso River Basin located in Tocantins State in northern Brazil. It is an important agricultural region where irrigation has an important role in rice and soybean crops, cultivated during the rainy and the dry seasons, respectively. The high levels of irrigation associated with below-average precipitation in 2016 and in the following years resulted in a water crisis in the Urubu Basin, with serious consequences to the environment and the economy of the region. This work evaluated the impact of reducing irrigation on environmental flows in the Urubu River Basin using hydrological modeling in WEAP. Irrigation water demand scenarios were simulated and analyzed from July 2018 through June 2019. Results indicated the need to reduce 35% of all water withdrawls in order to avoid the interruption of flow in the Urubu River Basin. This percentage was even greater when only some of the farmers cooperated. The paper emphasized that it is important that all farmers be involved and cooperate to reduce their water withdrawal by any means, including improving their irrigation system efficiency. The water regulator may also motivate water withdrawal reduction by modifying water permits and applying water withdrawal restrictions during the dry season.